Dynamics of the Farmers’ Terms of Trade and Macroeconomic Factors in the Agricultural Sector on the Island of Sulawesi: A Trend Analysis Approach - Non Botutihe; Mahludin H Baruwadi; Supriyo Imran (International Journal of Business and Quality Research, 2026)
The agricultural sector is a major economic pillar on Sulawesi Island, yet increases in macro-level production often do not correlate directly with farmers’ actual well-being at the field level. This study aims to analyze trends in key agricultural sector indicators on Sulawesi Island and map the influence of macro factors on farmers’ well-being. The method used is descriptive quantitative with a trend analysis approach utilizing secondary panel data from 6 provinces on Sulawesi Island over the period from 2012 to 2023. The variables observed include the Farmer’s Price Index (FPI), agricultural Gross Regional Domestic Product (GRDP), labor productivity, and agricultural sector inflation. The research results indicate a sharp polarization in agricultural economic performance across regions in 2023. West Sulawesi Province achieved the highest FER on record (121.47), driven by momentum in plantation commodity prices, despite being shaken by extreme inflation of 15.33% in 2021. Conversely, South Sulawesi Province established itself as a production giant with the highest agricultural GRDP (Rp72,266,300 million), but its per capita productivity remains low due to an agricultural structure that is still labor-intensive. Meanwhile, Gorontalo Province is the region with the most vulnerable purchasing power, trapped with an NTP below 100 (99.98), triggered by the massive conversion of rice fields and high inflation in production inputs. This study concludes that the slogan of increasing production is insufficient to improve farmers’ welfare without controlling rural inflation and ensuring price stability at the producer level.